Automatic Safety Electronic Saving Box - Fikri, Khairul; Fadlillah, Umi (Emitor: Jurnal Teknik Elektro, 2020)
In this modern era, many people save valuable items in their house, such as assets (jewelry and money) and important files. Therefore, saving box is the right and effective choice for protecting important goods if robbery or fire occurs someday. This final project is designing a saving box using different system than the general. The design of this system consists of several parts such as Wemos, D1 R1 (ESP8266), telegram, temperature sensor (DS18B20), keypad, power supply, android, buzzer and LCD. In this design, users are able to access (open) the saving box easily, such as entering the code into the keypad and controlling the saving box through an Android-based smartphone with the internet of things method, therefore by this method users can enter the code in any range both far or near. Then if a safe box gets robbery, the system will send a message to user. Meanwhile if fire occurs, the temperature sensor will detect it and also send a message to user. This design is expected to fulfill user’s need of a safer saving box.